2018
DOI: 10.1002/aah.10009
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Mortality of Age‐0 Smallmouth Bass in the Susquehanna River Basin, Pennsylvania

Abstract: Evidence of disease and mortalities of young of the year (age‐0) Smallmouth Bass Micropterus dolomieu has occurred during the late spring and summer in many parts of the Susquehanna River watershed since 2005. To better understand contributing factors, fish collected from multiple areas throughout the watershed as well as out‐of‐basin reference populations (Allegheny and Delaware River basins; experimental ponds, Kearneysville, West Virginia) were examined grossly and histologically for abnormalities. Tissue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 56 publications
0
31
1
Order By: Relevance
“…Coinfections with bacterial, viral and parasitic pathogens have been suggested to contribute to the mortality of YOY smallmouth bass and consequent declines in abundance (Walsh et al., ). However, the underlying environmental conditions contributing to increased pathogen prevalence/virulence or immunomodulation of the host fish are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Coinfections with bacterial, viral and parasitic pathogens have been suggested to contribute to the mortality of YOY smallmouth bass and consequent declines in abundance (Walsh et al., ). However, the underlying environmental conditions contributing to increased pathogen prevalence/virulence or immunomodulation of the host fish are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Ruptured cysts can release spores into the tissue eliciting inflammation (Walsh, Blazer et al., ). Subsequent research identified myxozoan cysts with similar morphology and tissue tropism, in the mouth, opercula and musculature (Walsh et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations